The effect of gestalt-based counseling on the level of self-esteem and intimate partner violence against pregnant women: A randomized control trial - Parinaz Noormohamadi; Atefeh Ahmadi; Yunes Jahani; Katayoun Alidousti (Wolters Kluwer Medknow Publications, 2021)
Background: Violence against women is a health problem that poses an additional threat to the mother and fetus during pregnancy. Therefore, the present study was conducted to investigate the effect of Gestalt counseling on self-esteem and Intimate Partner Violence (IPV) in pregnant women. Materials and Methods: This clinical trial was carried out on 60 pregnant women who were referred to health-care centers in Kerman, Iran, in 2018. Simple random sampling was performed through lottery. The intervention group (n = 30) received counseling in eight weekly sessions of 45 min using the Gestalt approach. The control group was placed on a waiting list. There was no blinding during the study. Data were collected using a demographic questionnaire, the Domestic Violence Questionnaire designed by Mohseni Tabrizi, and the Rosenberg Self-Esteem Scale before and after counseling. Results: Differences between the groups in terms of mean score of violence (intervention: t34 = 1.81, p = 0.08; control: t34 = 1.41, p = 0.16) and self-esteem (intervention: t34 = 1.87, p = 0.07; control: t34 = 1, p = 0.32) in the pretest and posttest were not significant. Analysis of covariance results showed a significant difference between the intervention 21.79 (10.62) and control groups 21.79 (10.62) in terms of mean (SD) violence (F1,67 = 1.97, p = 0.049) after the counseling sessions. It also showed a significant difference between the intervention 74.47 (14.61) and control groups 66.28 (15.14) in terms of self-esteem after the intervention (F1,67 = 5.02, p = 0.01). Conclusions: Considering the impact of the Gestalt approach on IPV and self-esteem, it is recommended that health-care providers be educated about using the Gestalt approach and apply it in communication with women.